Enhancing water use efficiency: Insights from hydrological variability encounter of multiple water sources and implications for terminal Lake management in arid regions - Kun Liu; Yunfei Chen; Bin Wu; Hailiang Xu; Abdul Waheed; Fan Gao; Bing He; Long Zhou; Jie Wu; Qin Zhang; Jinhao Ju (Ecological Indicators)
The escalating conflict between agricultural and ecological water demands, intensified by global climate change, poses significant challenges for water resource allocation in arid inland river basins. This study investigates the potential for integrated management of multiple water sources within the context of the Tarim River, Cherchen River, and Taitema Lake area. For the first time, we developed a joint distribution model of runoff for the Tarim and Cherchen Rivers, informed by the dynamics of Taitema Lake, to assess collaborative allocation strategies for terminal lake management in arid environments. Utilizing measured runoff data from 1960 to 2021, we employed a Bayesian vector autoregression model (BVAR) to analyze hydraulic connections between the rivers and the lake. Multivariate empirical mode decomposition (MEMD) was applied to identify periodic characteristics of runoff, while wavelet coherence transform assessed the consistency of runoff patterns. A Copula function was then utilized to construct a joint distribution model, quantifying variability patterns and their cascading effects on ecological water use in Taitema Lake. Findings reveal that the Cherchen River contributes more significantly to Taitema Lake than the Tarim River, exhibiting stable flows compared to the latter’s fluctuations. Significant lead-lag differences in flows were identified, with primary cycles of 2.9 years for the Tarim River and 5.7 years for the Cherchen River. The Copula model demonstrated a 44.52 % probability of synchronous wet-dry year occurrences, compared to 55.48 % for asynchronous occurrences. The complementarity between the Tarim River and the Cherchen River during wet and dry runoff encounter scenarios provides a foundation for establishing an efficient joint scheduling system and enhancing regional water use efficiency. This study underscores the critical role of strengthening multi-source water coordination and deepening understanding the dynamics of wet-dry runoff transitions to enhance water security and optimize resource management in arid regions.